USDA’s revised biotechnology regulation’s contribution to increasing agricultural sustainability and responding to climate change - Hoffman, Neil E. (Frontiers in Plant Science, 2022)
Biotechnology can provide a valuable tool to meet UN Sustainable Development Goals and U.S. initiatives to find climate solutions and improve agricultural sustainability. The literature contains hundreds of examples of crops that may serve this purpose, yet most remain un-launched due to high regulatory barriers. Recently the USDA revised its biotechnology regulations to make them more risk-proportionate, science-based, and streamlined. Here, we review some of the promising leads that may enable agriculture to contribute to UN sustainability goals. We further describe and discuss how the revised biotechnology regulation would hypothetically apply to these cases.